PHASE STRUCTURE IN AN ASYMMETRIC MODEL OF NUCLEAR MATTER - TRAN , HUU PHAT; LE , VIET HOA; LE , DUC ANH; NGUYEN , TUAN ANH; DINH , THANH TAM (Nuclear Science and Technology, 2012)
The phase structure of asymmetric nuclear matter in the extended Nambu - Jona-Lasinio (ENJL) model is studied by means of the effective potential in the one-loop approximation. It is found that the critical temperature for the liquid-gas phase transition decreases with increasing neutron excess. A typical firstorder phase transition of the liquid-gas transition occurs for y > 0:35 and eventually turns out to be second order for smaller y, here y is the proton fraction. PACS numbers: 11.30.Rd, 05.70.Fh, 21.65.-f.